Grain traits and ozone exposure shape maize resistance to Sitophilus zeamais - Ianne Lara O. de Meireles; Ana Caroline A. de Araújo; Catiane O. Souza; Fábio André G. S. Cavalcanti; Ernandes R. de Alencar; Jorge B. Torres; Raul Narciso C. Guedes; Cristina S. Bastos (Scientific Reports)
Abstract Maize plays a pivotal role in global food security, but post-harvest losses due to storage pests, particularly the maize weevil (Sitophilus zeamais), remain a significant challenge. This study evaluated resistance in 15 maize genotypes, including sweet corn, popcorn, and non-transgenic and transgenic varieties, while exploring the potential for synergistic effects of ozone treatment (direct or residual) in enhancing host plant resistance. Choice and no-choice trials were conducted to identify resistant genotypes, and resistance causes were analyzed in relation to grain chemical composition, color characteristics, and dimensions. Three genotypes representing varying resistance levels (susceptible, moderately and highly resistant) were tested for their response to ozone exposure. Among the tested genotypes, BAS 5802 (popcorn), 30s31 (non-Bt), 30s31VYHR (Bt), KWX 1002–1008 (non-Bt), and KWX 1010 (non-Bt) showed higher resistance in choice trials, while KWX 1005, 1007, 1010, 30s31, and 30s31VYHR were most resistant in no-choice trials. Combining ozone treatment with intermediate or highly resistant genotypes enhanced protection against S. zeamais. Increased grain color saturation and carbohydrate content contributed to resistance, whereas higher lipid and ash content correlated with increased susceptibility. These findings highlight the potential for integrating host plant resistance with ozone treatment as an innovative strategy for sustainable pest management.